Processing and characterization of calcined kaolin cement powder - Liew, Yun Ming; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Mohd Mustafa Al Bakri, Abdullah; Luqman, Musa, Dr.; Khairul Nizar, Ismail, Assoc. Prof. Dr.; Che Mohd Ruzaidi, Ghazali; Cheng, Yong Heah (Elsevier Ltd, 2013)
Link to publisher's homepage at http://www.elsevier.com/